Muhammad : a very short introduction - Brown, Jonathan (Jonathan A. C.) (Very short introductions ;, 2011)
An introduction to the major aspects of Muhammad's life and its importance, providing both Muslim and Western historical perspectives. It explains the prominent roles that Muhammad's persona has played in the Islamic world throughout history, from the medieval to the modern period.